Astrocyte Depletion Impairs Redox Homeostasis and Triggers Neuronal Loss in the Adult CNS - Schreiner, Bettina; Romanelli, Elisa; Liberski, Pawel; Ingold-Heppner, Barbara; Sobottka-Brillout, Bettina; Hartwig, Tom; Chandrasekar, Vijay; Johannssen, Helge; Zeilhofer, Hanns Ulrich; Aguzzi, Adriano; Heppner, Frank; Kerschensteiner, Martin; et al. (Cell reports (Cambridge), 2015)
Although the importance of reactive astrocytes during CNS pathology is well established, the function of astroglia in adult CNS homeostasis is less well understood. With the use of conditional, astrocyte-restricted protein synthesis termination, we found that selective paralysis of GFAP+ astrocytes in vivo led to rapid neuronal cell loss and severe motor deficits. This occurred while structural astroglial support still persisted and in the absence of any major microvascular damage. Whereas loss of astrocyte function did lead to microglial activation, this had no impact on the neuronal loss and clinical decline. Neuronal injury was caused by oxidative stress resulting from the reduced redox scavenging capability of dysfunctional astrocytes and could be prevented by the in vivo treatment with scavengers of reactive oxygen and nitrogen species (ROS/RNS). Our results suggest that the subpopulation of GFAP+ astrocytes maintain neuronal health by controlling redox homeostasis in the adult CNS. [Display omitted] •When adult GFAP+ astrocytes are depleted in vivo, motor skills are severely impaired•Neuronal loss occurs, whereas astroglial structural support still persists•Astroglial dysfunction disrupts CNS redox homeostasis, independent of microgliosis•Neutralization of ROS/RNS protects from neuronal injury Schreiner et al. examine the functional contribution of astrocytes to tissue homeostasis in the adult CNS and identify the redox-scavenging capacity of GFAP+ astrocytes as a key factor for neuronal health in vivo. The importance of the metabolic integrity of the glia-neuron interface highlights potential therapies for the treatment of neurodegenerative diseases.